OTH-06 Outcomes from the first formalised national endoscopy service in Sierra Leone. (June 2019) - Thomas-Macauley, DE; Conteh, S; Ngongo, F; Hancock, J; Mountford, C; Nylander, DL; Wells, CW; Bevan, R
Abstract : Introduction: Sierra Leone is a developing country in Africa, with a population of 7 million. Prior to 2016 there was no recognised endoscopy service in the country, although one hospital in the capital Freetown (pop. 1 million) owned an endoscopy stack. Medical services are rudimentary, but with a small group of motivated doctors and a grant from the BSG, a training programme was developed to support the provision of endoscopy. Here we describe the outcomes from the service since it's inception in December 2016. Methods: 3 endoscopists have been trained in OGD, and are supported remotely by 5 clinicians in the UK via Whatsapp. An annual training visit has been undertaken to consolidate skills. Weekly endoscopy lists are delivered in Choithram Hospital, with reports generated on ADAM endoscopy reporting software. An Excel spreadsheet database of all procedures is maintained by the endoscopists. The database was interrogated for procedures since the start of the service up to the end of January 2019. Data were collected on gender, age, intubation of the second part of the duodenum, length of procedure, CLO test results and endoscopic findings. Results: 289 procedures have been performed. 56% were male, median age 43 years (range 1–8). The number of procedures increased significantly in the second year of the service. The most frequent referral reason is dyspepsia (62%) Overall results are shown in table 1 . Pathology detection rates have been similar in each year of the programme. 18 cancers were identified, 25 cases with ulcers, and 21 cases with evidence of portal hypertensive changes (oesophageal/gastric varices, or portal gastropathy). Discussion: Sierra Leone now has a functioning upper GI endoscopy service. This service is providing high quality procedures, with overall D2 intubation rate meeting the JAG requirement of 95%. Pathology detection rates are high, possibly due to current practice of only those with the most severe symptoms being referred. Clinically important lesions (ulcers, cancers and complications of cirrhosis) are being detected, allowing patient care to be adjusted in light of these findings. As the service has developed, referral numbers have increased due to increased awareness and positive reputation developed by the service. The procedures have improved in quality, with a rising D2 intubation rate and a falling duration of procedure. These data demonstrate that an endoscopy service can be successful delivered, using innovative teaching methods and ongoing support delivered by a UK team. The endoscopists are now delivering training to new trainees, with a view to self sufficiency in training and expansion to other areas in Sierra Leone.